Social networks, attachment and integration: understanding the church attendance of Romanian migrants - Gherghina, Sergiu (Journal of beliefs and values, 2021)
Why do some migrants attend church more than others? This article uses an original survey conducted on first-generation Romanian migrants to identify the determinants of such a behaviour. Our study tests the explanatory power of three categories of determinants: migrants’ social network, their ties with the home country and the integration in the host society. The analysis uses individual-level data from a survey conducted on 1.839 Romanian migrants. We find that the contact with many migrants and high attachment to the home country lead to more frequent church attendance. At the same time, the presence in an organisation and the integration difficulties encountered in the host society steer migrants away from church. These results contribute to a better understanding of the diaspora dynamic in terms of religious behaviour and provide an assessment of how specific cultural manifestations are shaped.